SELF-MANAGEMENT AND SEVERITY OF ANGINA PECTORIS AMONG CORONARY HEART DISEASE PATIENT: HUBUNGAN MANAJEMEN DIRI DENGAN DERAJAT ANGINA PEKTORIS PADA PASIEN PENYAKIT JANTUNG KORONER - Huriani, Emil; Rahmi Meilani, Fitria; Lenggogeni, Devia Putri (Politeknik Kesehatan Kemenkes RI Jakarta I, 2025)
The prevalence of coronary heart disease (CHD) in Indonesia continues to increase. Padang ranks 10th with the most CHD patients in Indonesia. The clinical manifestation of CHD is angina pectoris. One of the efforts in minimizing angina pectoris is self- management. This study aimed to determine the relationship between self-management and the degree of angina pectoris in coronary heart disease patients at the cardiac polyclinic of RSUD dr. Rasidin Padang. This study used a quantitative research design with a cross-sectional approach. Sampling in this study used purposive sampling technique with 106 respondents. The instruments used were CSMS (Coronary self-management scale) and Canadian Cardiovascular Society angina grade (CCS). The results of univariate analysis showed that the patient's self-management was in the good range and the highest degree was in the angina II category. The bivariate analysis test using the chi-square correlation test showed a significant relationship between self-management and the degree of angina pectoris with significance 0.000 (? <0.005), meaning that there was a significant relationship between self-management and the degree of angina pectoris and coefficient relation was 0.95 (strong relation). The limitation of this study was the cross-sectional design used where the measurement of the dependent variable and the independent variable was carried out simultaneously so that it cannot prove the existence of cause and effect between the two variables. It is hoped that the hospital through health workers can increase health education in an effort to increase adequate knowledge related to self-management of coronary heart disease patients.